Recovery of Metallic Values from Brass Waste Using Bronsted Acidic Ionic Liquid as Leachate - Kilicarslan, Ayfer; Saridede, Muhlis Nezihi (SPRINGER, 2015)
The waste formed during industrial brass manufacturing is rich in copper and zinc metals. Therefore, treatment of this waste is a necessity from economic and environmental aspects. This study presents a process for recovery of zinc and copper through Bronsted ionic liquid (1-butyl-3-methyl-imidazolium hydrogen sulfate; [Bmim]HSO4), as leachate. It was found that all zinc content could be dissolved from the waste under two optimum conditions: (1) in ionic liquid (IL) concentration of 70% (v/v) at 60A degrees C in 30 min or (2) in IL concentration of 50% (v/v) at 100A degrees C in 60 min. On the other hand, ionic liquid leaching gave poor copper solubility under the conditions of the study. Zinc dissolution in the range 5-75 min by [Bmim]HSO4 can be explained with the shrinking core model controlled by diffusion through a product layer, and the apparent activation energy was calculated as 4.36 kJ/mol. The leach liquor was treated to obtain metallic zinc by the electrowinning method without a purification step. Scanning electron microscopy/energy dispersive x-ray spectroscopy (SEM/EDX) investigations showed that the layer of metallic zinc was plated successfully on the cathode.
Keywords: LEACHING KINETICS; COPPER; DISSOLUTION; ZINC; OPTIMIZATION; EXTRACTION; ULEXITE; GOLD; ORE; Materials Science; Metallurgy & Metallurgical Engineering; Mineralogy; Mining & Mineral Processing